Decomposition patterns of buried remains at different intervals in the Central Highveld region of South Africa. (July 2017) - Marais-Werner, A; Myburgh, J; Meyer, A; Nienaber, WC; Steyn, M
Burial of remains is an important factor when one attempts to establish the post-mortem interval as it reduces, and in extreme cases, excludes oviposition by Diptera species. This in turn leads to modification of the decomposition process. The aim of this study was to record decomposition patterns of buried remains using a pig model. The pattern of decomposition was evaluated at different intervals and recorded according to existing guidelines. In order to contribute to our knowledge on decomposition in different settings, a quantifiable approach was followed. Results indicated that early stages of decomposition occurred rapidly for buried remains within 7–33 days. Between 14 and 33 days, buried pigs displayed common features associated with the early to middle stages of decomposition, such as discoloration and bloating. From 33 to 90 days advanced decomposition manifested on the remains, and pigs then reached a stage of advanced decomposition where little change was observed in the next ±90–183 days after interment. Throughout this study, total body scores remained higher for surface remains. Overall, buried pigs followed a similar pattern of decomposition to those of surface remains, although at a much slower rate when compared with similar post-mortem intervals in surface remains. In this study, the decomposition patterns and rates of buried remains were mostly influenced by limited insect activity and adipocere formation which reduces the rate of decay in a conducive environment (i.e. burial in soil).